PENERAPAN ALGORITMA TEXTRANK DALAM MERANGKUM TEKS WORD DAN PDF - agustinus yovi siang (Universitas Lampung, 2024)
This review discusses the implementation of the TextRank algorithm for summarizing Word and PDF texts. Current technology enables rapid information growth but also raises issues regarding the lack of time to delve deeper into information. The TextRank algorithm is a web-based natural language processing method that employs an unsupervised approach and can be used to generate automatic text summaries. The search method used includes text preprocessing and the utilization of the TextRank algorithm. This article also explains how to use Google Colab and Google Drive to execute the TextRank algorithm for summarization. Steps for connecting Google Colab to Google Drive, installing Python libraries, retrieving data from Google Drive, and using the TextRank algorithm are also outlined in this article